Factors influencing meconium-stained amniotic fluid in West Guji, Oromia, Ethiopia: A cross-sectional study - Belda Negesa Beyene; Merga Hirbaye Jarso; Abebaw Kebede; Sena Belina Kitila (Elsevier, 2024)
Background: Meconium-stained amniotic fluid is an obstetric problem that occurs when a baby passes their first stool into the amniotic fluid before childbirth. It can indicate that the infant is under stress while the mother is giving birth. In addition to increasing the mother's risk of morbidity, meconium-stained amniotic fluid is linked to poor neonatal outcomes such as stillbirth, neonatal death, and meconium aspiration syndrome. However, there is currently little data on this issue. Therefore, the research aimed to determine the percentage of meconium-stained amniotic fluid and the contributing factors among women who gave birth at West Guji hospitals in Oromia, Ethiopia. Method: We surveyed 314 systematically selected women who gave birth between June 1st and July 30th, 2022. We collected information from their medical records and interviewed them. To code and enter the collected data, Epi Data version 4.6 was utilized. For both descriptive statistics and multivariable logistic regression analysis, SPSS version 25 was used. Statistical significance was declared at a p-value less than 0.05, a 95 % confidence interval, and an adjusted odd ratio. Results: In the current study, out of 314, 99 (29.4 %, 95 % CI = 24.6-34.6) women have meconium-stained amniotic fluid. Obstetric factors like premature rupture of membranes (AOR = 3.24, 95 % CI = 1.79-5.88), pregnancy-induced hypertension (AOR = 5.08, 95 % CI = 2.76-9.35), and non-reassuring fetal heart rate (AOR = 2.96, 95 % CI = 1.27-6.91) influenced meconium-stained amniotic fluid. Conclusion: The results of the current study emphasize the significance of close observation to identify possible signs of fetal distress during pregnancy and delivery. To protect the baby's health, pregnant women who have an early rupture of the membranes, high blood pressure, or a non-reassuring fetal heart rate should be closely observed. Early identification of these factors can help health care providers take steps to prevent or minimize complications related to meconium-stained amniotic fluid.